Teacher's professional practice and its complex network of subsystems joined into a co-formation environment (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2018)
Teacher’s professional practice is made up of a complex network of subsystems which play an essential role when getting started in the working environment in a dynamic and articulated way. These subsystems operate from the inside and contribute to the dominion of disciplinary, pedagogic, didactic and technological knowledge. They also contribute to the display of these types of knowledge when early graduated students have to face concrete situations of teaching. Each of these types of knowledge has particular problems that need to be identified in order to understand new paradigms that future teachers will have to face. Because of this, a professional practice should be considered as an environment in which knowledge that contributes to the acquisition of competences is gained. These types of knowledge will also help in the solution of problems that each subsystem has, as well as in the training of professionals who need to be capable of giving answers to working challenges. However, this can only be possible if co-formative practices that involve the intervention of different actors are taken into account. These co-formative practices should cooperate with the development of more certain and prudent practices.
Keywords: teacher’s professional practice; subsystems; co-formation; problematizing cores